ANALISIS STRUKTUR DAN CIRI KEBAHASAAN TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VII SMP NEGERI 18 PADANG - Dewi, Silvia Mardila; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
ABSTRACTÂ The purpose of this research is to describe the text structure of the report of the observation and describe the text of the observation report of class VII from SMP Negeri 18 Padang. This type of research is qualitative research with a descriptive method. The data source in this study is the text of the observation of students of class VII SMP Negeri 18 Padang, written by students in grades VII. 2 numbering thirty texts. The instruments in this study are researchers themselves. Data is analyzed by describing, analyzing, and discussing data based on theory. The results of this study are first, in the text of the observation of students of class VII SMP Negeri 18 Padang is found three text structures of observation results report, namely general definition, section description, and conclusion. Secondly, in the text of the observation of class VII students SMP Negeri 18 Padang, generally students have used the fourth feature of the text of observation report. It can be concluded that the structure and characteristics of the text in the observation report of grade VII students SMP Negeri 18 Padang is good. It can be seen from the thirty texts of the observation report analyzed, twenty-six texts of the observation report already has a complete structure and of the thirty text of the observation report analyzed, the twenty-four texts have used the full text feature of the observation report.Â Kata kunci: Struktur, Ciri Kebahasaan, Teks Laporan Hasil Observas